Customer Base Brand Equity Approach and Consumer Loyalty of Purchasing Decisions on Online Shopping in Indonesia - Kayani Putri Bestari, Dinda; Gusni; Agustriyana, Dervish; Anderson Butarbutar, DJ (International Journal of Psychosocial Rehabilitation, 2020)
In the digitalization era, the Indonesian people were very fond of the type of online shopping, and this was seen as an opportunity for e-commerce companies. Data on the number of visitors for each e-commerce website has increased, but this has not been offset by increased revenue. Some e-commerce companies have the highest ranking on the number of visitors, but the revenue earned does not reflect that position. This indicates that there is a mismatch between the number of website visitors and the revenue earned by each company. Is the increasing number of visitors an effect of good customer base brand equity, why this does not have an impact on the addition of reports in each company, and how the influence of customer base brand equity and customer loyalty towards purchasing decisions in online shopping—various questions above can be answered through this research. The survey was conducted on 100 respondents who were consumers of Lazada e-commerce in parts of West Java and DKI Jakarta, namely the cities of Bandung, Bogor, Depok, Tangerang, Bekasi, Garut, Tasikmalaya, and Sumedang. The survey results were obtained using Partial Least Square (PLS-SEM), a type of construct with a reflexive indicator. Based on the analysis, the findings are: (1) Customer-based brand equity has a positive and significant effect on online purchases, especially for Lazada. (2) Consumer loyalty, consisting of cognitive loyalty, affective loyalty, connective loyalty, and action loyalty, has a negative effect on purchase decisions but has a significant influence on the formation of purchase decisions on online purchases.